The Effect of a Training Video With Audio Description on the Breast Self-Examinations of Women With Visual Impairments. (January 2023) - Çelik, Sultan; Çalım, Selda İldan
Introduction: Breast cancer is a significant health problem affecting the health of women globally. Breast self-examination is a procedure applied for the early detection of breast cancer. Given the barriers that women with visual impairments face to access health care and health education, there is a need to develop materials for breast self-examination training as a skills-based practice for this group. This study evaluated the effect of a training video with an audio description on the breast self-examination of women who were visually impaired.Methods: The universe of this quasi-experimental study comprised women who were visually impaired ( N  = 70) who were registered members of the Manisa Altinokta Blind Association in Turkey. The women who participated in the study volunteered and met the selection criteria ( n  = 60). They were divided into two groups by lot. The audio description group listened to a breast self-examination training video with an audio description ( n  = 30). The control group listened to the training video accompanied by typical sound, without audio description ( n  = 30). Before and after a training video, all women performed breast self-examination on a female mannequin torso. The skills of women in breast self-examination were evaluated using a checklist by a midwife who was non-researcher.Results: The skills differed significantly between the two groups after the video training ( p < 0.05). The audio description group correctly performed most of the skills required for breast self-examination. None of the women in the groups were able to apply steps for such self-examination before the training.Discussion: A breast self-examination training video with audio description can improve the self-examination skills of women with visual impairments.Implications for Practitioners: Women with visual impairments benefit from watching a breast self-examination training video with an audio description before performing self-examinations. Training videos with audio descriptions should, therefore, be prepared for the health education of individuals who are visually impaired.